2016
DOI: 10.1097/mcg.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitive C-Reactive Protein as a Marker for Inflammation in Irritable Bowel Syndrome

Abstract: Background Recent studies demonstrated low-grade inflammation in patients with Irritable Bowel Syndrome (IBS). However, these studies have been relatively small and do not enable examination of this factor in different subtypes of IBS and the possibility of confounding effects of co-morbidities that may be associated with inflammatory responses. Goals To investigate the association between high sensitive C - reactive protein (hs-CRP) and the diagnosis of IBS, IBS-subtypes, symptoms' severity and IBS-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 37 publications
3
29
2
Order By: Relevance
“…These studies indicated that HS-CRP is higher in IBS patients compared to healthy controls and these levels were highest in IBS-D and in those patients with greater IBS severity 72,73 . These findings also need to be confirmed in larger studies.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 87%
See 1 more Smart Citation
“…These studies indicated that HS-CRP is higher in IBS patients compared to healthy controls and these levels were highest in IBS-D and in those patients with greater IBS severity 72,73 . These findings also need to be confirmed in larger studies.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 87%
“…These findings also need to be confirmed in larger studies. Based on the latest publication 73 , the median HS-CRP levels in the IBS group and healthy controls were 1.80 and 1.20 mg/L, respectively, with large interquartile ranges questioning the clinical value of HS-CRP in differentiating IBS from healthy controls.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
“…However, it is worth emphasizing that although one or more of these mechanisms are evident in most IBS patients, none, including inflammation hypothesis, can account for the symptoms in all cases. However, studies exploring the possible role of inflammation in the pathogenesis of IBS continue to draw the attention of many researchers in the field [30].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Data in literature emphasize the role of inflammation, even subclinical, in the pathogenesis of IBS [26]. …”
Section: Introductionmentioning
confidence: 99%